Brazilian cacti potential in the gastronomy: a review (Research, Society and Development, 2022)
Cactaceae have important nutritional composition and physicochemical characteristics, although their use in human food remains little recognized. The present study aimed to describe the application and potential of the five main cacti of the Caatinga biome (mandacaru, facheiro, xiquexique, corona de frade and palm) in gastronomy, in the context of chefs' creations, and to present scientific data on the development of new products based on these natural resources. For this, an exploratory qualitative research was carried out, based on a bibliographic review, which addressed: (i) considerations about the Caatinga biome from the perspective of strengthening regional gastronomy and the creation of preparations with cactus by recognized Brazilian chefs and (ii) presentation of scientific papers on the development of new food products from these plants. As a result, the facheiro, xiquexique, mandacaru cactaceae stood out among the others, with greater multifunctional applications, in addition to being used in the production of juices, sweets, ice cream, flour, pigment extraction, bakery and pasta products, dairy products, fermented beverages. alcoholics and probiotics. Thus, it was observed that cacti have a great nutritional potential in human food, highlighting gastronomy as an important partner in this process. In this segment, there is a need to invest in studies that converge towards the development of technologies capable of favoring the processing of cacti, in order to value and encourage their use in culinary preparations, subsidizing the development of sustainable gastronomy in the Caatinga biome.